2017
DOI: 10.1016/j.neurobiolaging.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

ApoE influences regional white-matter axonal density loss in Alzheimer's disease

Abstract: Mechanisms underlying phenotypic heterogeneity in young onset Alzheimer disease (YOAD) are poorly understood. We used diffusion tensor imaging and neurite orientation dispersion and density imaging (NODDI) with tract-based spatial statistics to investigate apolipoprotein (APOE) ε4 modulation of white-matter damage in 37 patients with YOAD (22, 59% APOE ε4 positive) and 23 age-matched controls. Correlation between neurite density index (NDI) and neuropsychological performance was assessed in 4 white-matter regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 53 publications
6
100
0
Order By: Relevance
“…Previous works have shown that NODDI could be more sensitive than DTI for detecting white matter changes related to ageing24 or young-onset Alzheimer’s disease 25. Here, for the first time, we showed that NODDI outperformed DTI for identifying white matter abnormalities during the presymptomatic stage of a neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous works have shown that NODDI could be more sensitive than DTI for detecting white matter changes related to ageing24 or young-onset Alzheimer’s disease 25. Here, for the first time, we showed that NODDI outperformed DTI for identifying white matter abnormalities during the presymptomatic stage of a neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 57%
“…This potential for greater tissue specificity has motivated application of NODDI in a few neurodegenerative disease studies 25 29–32. In young-onset Alzheimer’s disease, one study showed widespread NDI reduction and regional ODI reduction in the corpus callosum and internal capsule of patients 25. In Parkinson’s disease, another study observed reduced NDI in the substantia nigra and putamen of patients 31.…”
Section: Discussionmentioning
confidence: 99%
“…While such models (e.g., neurite orientation dispersion and density imaging) qualitatively demonstrate similar trends that reflect known white-matter ontogeny and pathology (e.g., Billiet et al, 2015; Slattery et al, 2017), quantitative estimates derived from various models are model-dependent and remain subject to the limitations of model assumptions, wherein accuracy is sacri- ficed for biological interpretability (Jelescu et al, 2015). More comprehensive diffusion data sets with higher b-values may over- come these limitations, but these acquisitions come at the expense of clinical feasibility.…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of NODDI is indisputable, with applications to a very large panel of brain alterations and pathologies (Adluru et al, 2014; Churchill et al, 2017; Kunz et al, 2014; Okita et al, 2017; Schneider et al, 2017; Slattery et al, 2017; Wen et al, 2015). However, there are important assumptions within NODDI related to its design that have strong implications to its specificity.…”
Section: Modelsmentioning
confidence: 99%